2017
DOI: 10.1038/s41394-017-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Retraining walking adaptability following incomplete spinal cord injury

Abstract: IntroductionFunctional walking requires the ability to modify one’s gait pattern to environmental demands and task goals—gait adaptability. Following incomplete spinal cord injury (ISCI), gait rehabilitation such as locomotor training (Basic-LT) emphasizes intense, repetitive stepping practice. Rehabilitation approaches focusing on practice of gait adaptability tasks have not been established for individuals with ISCIs but may promote recovery of higher level walking skills. The primary purpose of this case se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In mammalian (e.g., human) spinal cord injury, substantial recovery of locomotory function can be observed depending on the level of injury and age of the subject (Tillakaratne et al, 2010;Rossignol and Frigon, 2011;Pizzolato et al, 2021). However, it is not known whether the robustness, an ability to withstand external perturbations, is also restored along with recovery of the locomotion, e. g., obstacles (van Hedel et al, 2005;Fox et al, 2017). In the present study, we assessed the ability of a well-known rhythm-generating network, the Cancer borealis pyloric network, to homeostatically recover the robustness of its neural activity to external perturbations after the activity has been severely disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian (e.g., human) spinal cord injury, substantial recovery of locomotory function can be observed depending on the level of injury and age of the subject (Tillakaratne et al, 2010;Rossignol and Frigon, 2011;Pizzolato et al, 2021). However, it is not known whether the robustness, an ability to withstand external perturbations, is also restored along with recovery of the locomotion, e. g., obstacles (van Hedel et al, 2005;Fox et al, 2017). In the present study, we assessed the ability of a well-known rhythm-generating network, the Cancer borealis pyloric network, to homeostatically recover the robustness of its neural activity to external perturbations after the activity has been severely disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…The SCI-FAP is a valid, reliable, and responsive measure of walking skills for adults with SCI [13,14]. It has been used in research to validate multiple assessment tools [15,16] and to measure walking capacity during or after interventions [17][18][19][20][21]. The original SCI-FAP consists of seven tasks and it has been reduced to four tasks in the Modified SCI-FAP [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In iSCI patients training precision stepping has been shown to improve walking capacity measured with the SCI functional ambulation profile [SCI-FAP, ( 24 )]. More recently, however, Fox and colleagues concluded that the efficacy of gait adaptability training on walking and balance function should be further investigated ( 25 ).…”
Section: Introductionmentioning
confidence: 99%